Increased Amazon freshwater discharge during late Heinrich Stadial 1. (1st February 2018) - Crivellari, Stefano; Chiessi, Cristiano Mazur; Kuhnert, Henning; Häggi, Christoph; da Costa Portilho-Ramos, Rodrigo; Zeng, Jing-Ying; Zhang, Yancheng; Schefuß, Enno; Mollenhauer, Gesine; Hefter, Jens; Alexandre, Felipe; Sampaio, Gilvan; et al.
Abstract: The temporal succession of changes in Amazonian hydroclimate during Heinrich Stadial 1 (HS1) (ca. 18–14.7 cal ka BP) is currently poorly resolved. Here we present HS1 records based on isotope, inorganic and organic geochemistry from a marine sediment core influenced by the Amazon River discharge. Our records offer a detailed reconstruction of the changes in Amazonian hydroclimate during HS1, integrated over the basin. We reconstructed surface water hydrography using stable oxygen isotopes (δ 18 O) and Mg/Ca-derived paleotemperatures from the planktonic foraminifera Globigerinoides ruber, as well as salinity changes based on stable hydrogen isotope (δD) of palmitic acid. We also analyzed branched and isoprenoid tetraether concentrations, and compared them to existing bulk sediment ln(Fe/Ca) data and vegetation reconstruction based on stable carbon isotopes from n- alkanes, in order to understand the relationship between continental precipitation, vegetation and sediment production. Our results indicate a two-phased HS1 (HS1a and HS1b). During HS1a (18–16.9 cal ka BP), a first sudden increase of sea surface temperatures (SST) in the western equatorial Atlantic correlated with the slowdown of the Atlantic Meridional Overturning Circulation (AMOC) and the associated southern hemisphere warming phase of the bipolar seesaw. This phase was also characterized by an increased delivery of terrestrial material. During HS1b (16.9–14.8 cal ka BP), a decrease in terrestrial input was, however, associated with a marked decline of seawater δ 18 O and palmitic acid δD. Both isotopic proxies independently indicate a drop in sea surface salinity (SSS). A number of records under the influence of the North Brazil Current, in contrast, indicate increases in SST and SSS resulting from a weakened AMOC during HS1. Our records thus suggest that the expected increase in SSS due to the AMOC slowdown was overridden by a two-phased positive precipitation anomaly in Amazonian hydroclimate.